Implikasi Pembatalan Perkawinan Terhadap Status dan Pembagian Harta Bersama Menurut Hukum Perdata Indonesia - Wijaya, Dody; Wahyudi, Wahyudi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
This study analyzes the implications of marriage annulment on the status and division of joint property under Indonesian civil law. The research focuses on the dichotomy between the legal fiction in Article 28 of the Marriage Law, which states that everything applies "as if the marriage never existed," and the empirical reality of accumulated joint assets during the marriage. Using a normative legal research method, this study examines the legal vacuum created by this fiction, leading to uncertainty regarding the status of property. The findings indicate that in practice, the Supreme Court through its jurisprudence (e.g., Supreme Court Decision No. 105 K/Pdt/2016) overcomes this impasse by applying the legal construct of a civil partnership (maatschap) from the Civil Code as a basis for fair division. However, this approach still faces significant problems, including proving the origin of assets, protecting third parties in good faith, and the vulnerability of parties with non-financial contributions. The research concludes by emphasizing the urgency for legal clarification through the harmonization of jurisprudence or legislative reform to ensure legal certainty and justice for all involved parties.